TI_GERICHTE 14.2011.202 vom 23. Januar 2012 , Reclamo contro la dichiarazione di fallimento. Solvibilitâ resa verosimile - TI Tribunale d'appello (2012)
Reclamo contro la dichiarazione di fallimento. Solvibilitâ resa verosimile